Effects of Homocysteine and Hyperglycemia on the Proliferation of Aortic Vascular Smooth Muscle Cells of Obese Type 2 Diabetes Rat - Hyung Joon Yoo (Annals of Geriatric Medicine and Research, 2017)
Background : The aim of this study was to investigate the role of homocysteine on the proliferation of rat aortic vascular smooth muscle cells (VSMCs) by measuring mitogen-activated protein (MAP) kinase under hyperglycemic conditions. Methods : Rat aortic VSMCs were isolated from Otsuka Long-Evans Tokushima Fatty and Long-Evans Tokushima Otsuka rats. VSMCs were incubated in the presence of homocysteine (1 mM) with/without PD98059 (30 μM) and wortmannin (300 nM) for 48 hours in different concentrations of glucose (5.5, 25 mM). Proliferation was evaluated by methylthiazoletetrazolium (MTT), fluorescence-activated cell sorting (FACS), and western blot analyses. Results : In MTT and FACS analyses, the proliferation of VSMCs was increased by homocysteine. After PD98059 (30 μM) and wortmannin (300 nM) treatment with homocysteine (1 mM), the increased proliferation of VSMC caused by homocysteine, decreased to control levels. In Western blot analysis, immunoexpression of phospho-p44/42 MAP kinase was significantly increased by homocysteine (1 mM). After PD98059 and wortmannin treatment, the increased immunoexpression of phospho-p44/42 MAP kinase was suppressed. Conclusion : These results suggest that the MAP kinase and PI3 kinase pathways are the main mechanisms involved in rat VSMC proliferation caused by homocysteine under hyperglycemic conditions.